Effectiveness and Usefulness of Personal Tax Reliefs: A Study of Ghana Revenue Authority’s Domestic Tax Division - Agbemava, Edinam; Bediako, Albert K.; Nyarko, Israel Kofi (Asian Journal of Economics and Empirical Research, 2016)
This study examined the effectiveness and usefulness of personal tax relief administration in Ghana and the challenges facing the Ghana Revenue Authority Domestic Tax Division in the quest to meet its personal tax administration objects. Questionnaires were administered to twenty taxpaying persons and ten tax officials from the Ghana Revenue Authority (Domestic Tax Division) in the Volta Region of Ghana. Statistical package for social sciences software was used to analyze data gathered. The study found that the administration of personal tax reliefs is very helpful to the tax payer but it is not effective as it should be. Inadequate tax education, improper completion of IT forms 21 and 51, and low staff motivation were identified as key reasons for the ineffectiveness. Recommendations are however provided and if they are well implemented, would solve the problems of administration of personal tax reliefs.